A new species of the Pristimantis orestes group (Amphibia: Strabomantidae) from the high Andes of Ecuador, Reserva Mazar - Guayasamin, Juan M.; Arteaga, Alejandro F. (Zootaxa, 2013)
We describe a new Pristimantis from La Libertad and Rumiloma, Reserva Mazar, Andes of Southeastern Ecuador, at elevations between 2895–3415 m. This species is assigned to the P. orestes group, from whose members it differs by its small body size (adult males ≤ 18.1 mm; adult females ≤ 23.7 mm), usually reticulated ventral pattern, and visible tympanum. The vocalization of the new species consists of a series of calls; each call is composed by a pulsed, non-modulated note in frequency, and with a dominant frequency of 3122–3171 Hz. A molecular phylogeny based on a fragment of the mitochondrial gene 12S shows that the new species is sister to Pristimantis simonbolivari.